Folk-archiving Minor Audiovisual Contents. Television Programs, Pirate Care and Shadow Libraries - Rasmi, Jacopo (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
Sometimes TV is archived by amateurs. Sometimes TV is an interesting source to build experimental libraries of minor audiovisual contents. Sometimes the best way to preserve certain memories of cinema is to record the programs broadcast in order to upload them on informal platforms. These digital ecosystems are called “shadow libraries” and are fostered by gesture of “folk archiving” (Goldsmith). Behind and beyond the construction of an audiovisual heritage defined by State policies or commercial forces, a collective “pirate care” (Graziano, Medak & Mars) allows the preservation and the democratic distribution of rare contents.